2020
DOI: 10.1002/smll.202000299
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Dose Silver Nanoparticle Surface Chemistry and Temporal Effects on Gene Expression in Human Liver Cells

Abstract: Silver nanoparticles (AgNPs) are widely incorporated into consumer products and used medically for their biocidal properties, [1] with applications in biosensing, imaging, and therapies. As concerns of frequent and cumulative exposures increase, AgNP toxicity has drawn considerable attention. [2,3] Most exposure studies to date involve atypical high-dose concentrations Silver nanoparticles (AgNPs) are widely incorporated into consumer and biomedical products for their antimicrobial and plasmonic properties wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Surface modification of AgNPs can significantly affect their biocompatibility and their interaction with cells [ 39 ]. House et al observed that AgNPs modified with branched BPEI had a more significant gene-regulatory effect than unmodified particles [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surface modification of AgNPs can significantly affect their biocompatibility and their interaction with cells [ 39 ]. House et al observed that AgNPs modified with branched BPEI had a more significant gene-regulatory effect than unmodified particles [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Silver ions and several silver-based nanomaterials display toxicity ( 3 , 6 , 8 ). Therefore, we sought to determine whether other silver materials could inhibit DNA replication in cell-free extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Silver nanomaterials are routinely incorporated into medical and consumer products due to their excellent antimicrobial capacities ( 1 , 2 ). Therefore, it is important to assess how they interact with macromolecules during biological processes such as DNA transactions to better understand their potential toxicity ( 3 ). The biological properties and potential toxic effects of silver nanomaterials are governed by multiple physicochemical factors including shape, size, dose and surface coating ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the potential side‐effects and toxicity of some metal and carbon nanomaterials on health are worrying and noteworthy. 127 , 128 More biocompatible and advanced nanobiotechnologies using biodegradable biomaterials, such as biopolymers and polypeptides, should be developed to solve current problems in nanobiotechnological methods. Overall, although there are limitations now, nanobiotechnologies have laid out their opportunities for the war against COVID‐19.…”
Section: Perspectives and Current Challengesmentioning
confidence: 99%
“…More practical design strategy should be considered by scientists for meeting the sustained outbreak and fast spread of SARS‐CoV‐2. In addition, the potential side‐effects and toxicity of some metal and carbon nanomaterials on health are worrying and noteworthy 127,128 . More biocompatible and advanced nanobiotechnologies using biodegradable biomaterials, such as biopolymers and polypeptides, should be developed to solve current problems in nanobiotechnological methods.…”
Section: Perspectives and Current Challengesmentioning
confidence: 99%